Cap-assisted colonoscopy: a meta-analysis of high-quality randomized controlled trials - Nutalapati, Venkat; Kanakadandi, Vijay; Desai, Madhav; Olyaee, Mojtaba; Rastogi, Amit (Endoscopy International Open, 2018)
Background and study aims Standard colonoscopy (SC) is the preferred modality for screening for colon cancer; however, it carries a significant polyp/adenoma miss rate. Cap-assisted colonoscopy (CC) has been shown to improve polyp/adenoma detection rate, decrease cecal intubation time and increase cecal intubation rate when compared to standard colonoscopy (SC). However, data on adenoma detection rate (ADR) are conflicting. The aim of this meta-analysis was to compare the performance of CC with SC for ADR among high-quality randomized controlled trials. Patients and methods We performed an extensive literature search using MEDLINE, EMBASE, Scopus, Cochrane and Web of Science databases and abstracts published at national meetings. Only comparative studies between CC and SC were included if they reported ADR, adenoma per person (APP), cecal intubation rate, and cecal intubation time. The exclusion criterion for comparing ADR was studies with Jadad score ≤ 2. The odds ratio (OR) was calculated using Mantel-Haenszel method. I2 test was used to measure heterogeneity among studies. Results Analysis of high-quality studies (Jadad score ≥ 3, total of 7 studies) showed that use of cap improved the ADR with the results being statistically significant (OR 1.18, 95 % CI 1.03 – 1.33) and detection of 0.16 (0.02 – 0.30) additional APP. The cecal intubation rate in the CC group was 96.3 % compared to 94.5 % with SC (total of 17 studies). Use of cap improved cecal intubation (OR 1.61, 95 % CI 1.33 – 1.95) when compared to SC (P value < 0.001). Use of cap decreased cecal intubation time by an average of 0.88 minutes (95 % CI 0.37 – 1.39) or 53 seconds. Conclusions Meta-analysis of high-quality studies showed that CC improved the ADR compared to SC.